The Impact of Economic Nationalism Policies on Global Cooperation: A Case Study of The Covid-19 Pandemic - Abdul Somad; Fatmawati Fatmawati (Leges Privatae, 2024)
This study analyzes the impact of Indonesia's economic nationalism policy on global cooperation during the COVID-19 pandemic. By implementing policies such as import restrictions, domestic sector incentives, and local product promotion, Indonesia aims to protect the national economy and reduce dependence on foreign products. Although these policies help strengthen the domestic economy, their impact on international trade relations and foreign direct investment (FDI) is quite significant. The decline in FDI in 2020 and tensions with trading partners related to protectionist policies are major challenges for Indonesia's global economic cooperation. This study uses a qualitative approach with data collection techniques through literature studies and analysis of government policy documents, as well as secondary data from scientific articles and international reports. The results of the study indicate that Indonesia's economic nationalism policy provides short-term benefits for economic stability, but poses risks to international competitiveness and long-term economic cooperation.